Efficacy of melatonin as adjunctive therapy for sepsis: A meta-analysis of randomized controlled trials - Zhuangzhuang Sun; Cheng Yu; Zhaopeng Zhang; Chunjie Hu; Xin Li; Xiheng Dong; Ru Zhang; Zhirun Zhang; Tonggang Zhu; Xin Su; Junpeng Guo (Complementary Therapies in Medicine, 2025)
Background: This study systematically evaluates the therapeutic efficacy of melatonin as an adjunctive therapy, aiming to determine its potential to reduce mortality and mitigate inflammatory responses in patients with sepsis. Methods: A search was conducted across PubMed, Web of Science, Cochrane Library, and Embase databases. The Cochrane Collaboration Risk of Bias (ROB) tool was systematically employed to assess the potential for bias in the relevant studies. The I² statistic was employed to evaluate heterogeneity among the studies. Potential publication bias was assessed using Begg's test. Sensitivity analysis was performed to examine the stability of the results. Additionally, a GRADE evaluation of the evidence level. Results: This meta-analysis encompassed a total of seven randomized controlled trials involving 421 patients diagnosed with sepsis. The primary results indicated that the mortality rate in the intervention group was significantly lower than that in the control group, suggesting that melatonin may effectively reduce mortality among sepsis patients [OR = 0.42, 95 % CI: 0.23–0.77, P = 0.005]. Additionally, the CRP levels in the intervention group were markedly lower than those in the control group, providing evidence that melatonin possesses anti-inflammatory properties that may help decrease inflammatory markers in sepsis patients [SMD= -4.00, 95 % CI: −6.47 to −1.53, P = 0.001]. Furthermore, Secondary outcome results showed no statistically significant differences in sequential organ failure assessment (SOFA) scores, length of hospital stay, and adverse effects. A sensitivity analysis confirmed the robustness of the findings from the included studies. By applying the GRADE system to evaluate the quality of evidence, we found the evidence in four grades: one rated as high quality, one as medium quality, and three rated as low quality. Conclusion: Melatonin, when used as an adjuvant therapy, significantly reduces mortality and lowers the levels of the inflammatory marker CRP in patients with sepsis, while also improving their physical condition. However, due to the limited number and quality of the articles, these conclusions warrant further verification through the conduct of additional high-quality research.